Design, assembly and characterization of silicide-based thermoelectric modules. (15th February 2016) - Skomedal, Gunstein; Holmgren, Lennart; Middleton, Hugh; Eremin, I.S.; Isachenko, G.N.; Jaegle, Martin; Tarantik, Karina; Vlachos, Nikolas; Manoli, Maria; Kyratsi, Theodora; Berthebaud, David; Dao Truong, Nhi Y.; et al.
Highlights: Novel silicide-based thermoelectric modules were experimentally investigated. The modules produced high power of 1.04 W at 405 °C and 3.24 W at 735 °C. An estimated module efficiency of 5.3% represent the highest reported for silicide systems. Abstract: Silicides have attracted considerable attention for use in thermoelectric generators due mainly to low cost, low toxicity and light weight, in contrast to conventional materials such as bismuth and lead telluride. Most reported work has focused on optimizing the materials properties while little has been done on module testing. In this work we have designed and tested modules based on N-type magnesium silicide Mg2 (Si–Sn), abbreviated MGS, and P-type Higher Manganese Silicide, abbreviated HMS. The main novelty of our module design is the use of spring loaded contacts on the cold side which mitigate the effect of thermal expansion mismatch between the MGS and the HMS. We report tests carried out on three modules at different temperatures and electric loads. At a hot side temperature of 405 °C we obtained a maximum power of 1.04 W and at 735 °C we obtained 3.24 W. The power per thermoelectric material cross section area ranged from 1 to 3 W cm − 2 . We used the modeling tool COMSOL to estimate efficiencies at 405 and 735 °C and obtained values of 3.7% and 5.3% respectively – to our knowledge the highest reported value to date for silicide based modules. Post-test examination showed significant degradation of the N-type (MGS) legs at the higher hot side temperatures. Further work is underway to improve the lifetime and degradation issues.